THE FREIE RECHTSBEWEGUNG MOVEMENT’S VIEW ON COURT RULINGS REGARDING INTERFAITH MARRIAGES: PANDANGAN ALIRAN FREIE RECHTSBEWEGUNG TERHADAP PENETAPAN PENGADILAN ATAS PERKAWINAN BEDA AGAMA - Djumikasih (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2026)
Interfaith marriage is a topic that has been endlessly discussed for a long time. Even now, this legal issue is always interesting to debate, because in Indonesian society there are often pros and cons. Not only among the public, court decisions regarding requests for interfaith marriages also differ, some grant them and some reject them. To answer this problem, the author discusses the validity of interfaith marriages according to the religions recognized in Indonesia, because the validity of marriages in Indonesia is based on the laws of each religion and belief. From the results and discussion, it can be concluded that all religions in Indonesia, whether Islam, Christianity, Catholicism, Hinduism, Buddhism or Confucianism, regulate marriage should be carried out by couples of the same religion, because marriage is an expression of religion itself. Therefore, basically all religions in Indonesia prohibit interfaith marriages, only some prohibit it explicitly but there are also those that prohibit it implicitly. Therefore, interfaith marriages in Indonesia are invalid.